The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/dar.13145
|View full text |Cite
|
Sign up to set email alerts
|

Self‐perception of assisting with future injection drug initiation: The influence of relationships in the process of drug injecting initiation

Abstract: Introduction and AimsPeople who inject drugs (PWID) play critical roles in assisting others into injection drug use (IDU) initiation. Understanding perceptions of PWID's risk of initiating others is needed to inform interventions for prevention. The objective was to examine factors associated with self‐perception of assisting with future IDU initiation events. The primary variables of interest are the relationships of PWID with the person(s) they assisted and their reasons for previously providing initiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Our finding that 17% of PWID in our sample reported having provided injection initiation assistance in the past 6 months aligns with existing research; however, among persons who reported having recently initiated a non-injector, more than 35% reported they would be likely to do so again in the future. This proportion is significantly greater than rates found among PWID residing in more urban areas; for example, a recent study found that among PWID who had ever provided injection initiation assistance in Tijuana (Mexico), Vancouver (Canada), and San Diego (USA), 26.1%, 16.8%, and 14.7%, respectively, reported they would likely initiate someone in the future [ 68 ]. In contrast, a study in Los Angeles and San Francisco (USA) found that 66% of PWID who provided injection initiation assistance in the past year reported being likely to initiate others in the future [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that 17% of PWID in our sample reported having provided injection initiation assistance in the past 6 months aligns with existing research; however, among persons who reported having recently initiated a non-injector, more than 35% reported they would be likely to do so again in the future. This proportion is significantly greater than rates found among PWID residing in more urban areas; for example, a recent study found that among PWID who had ever provided injection initiation assistance in Tijuana (Mexico), Vancouver (Canada), and San Diego (USA), 26.1%, 16.8%, and 14.7%, respectively, reported they would likely initiate someone in the future [ 68 ]. In contrast, a study in Los Angeles and San Francisco (USA) found that 66% of PWID who provided injection initiation assistance in the past year reported being likely to initiate others in the future [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants reported if they had injected someone for their first injection in the past 6 months (yes/no). This measure was included as related research has found associations between persons having previously provided injection initiation assistance and perceptions that they would assist others in the future [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…(Clara) "Cassie's" experience noted here demonstrates that the injection initiation event is not necessarily a coercive or bad experience, and that it can be completed within a caring environment. In the quote above she noted that an experienced WWID helped her and friends, implying that she was concerned for naïve users and wanted to help them inject safely and properly (Bloom et al, 2021;Tuchman, 2015). It could also be theorized that although women are most likely to be injected by intimate male partners that this is not necessarily a coercive experience with male partners giving in to demands from women, partly due to fears that they will inject unsafely if left to try it by themselves (Rhodes et al, 2017;Simmons et al, 2012).…”
Section: Injection Initiationmentioning
confidence: 99%
“…Although there is extensive literature on drug use trajectories and transition to injection among people who use drug users worldwide (Ambekar et al, 2019;Baluku, Wamala, & Muhangi, 2019;Bluthenthal, Wenger, Chu, Bourgois, & Kral, 2017;Brecht, Huang, Evans, & Hser, 2008;Horyniak et al, 2015;Hser, 2007;Koozegar, Shahesmaeili, & Noroozi, 2018;Neaigus et al, 2001;Oliveira et al, 2006;Roy et al, 2003;Vidal-Trecan, Varescon-Pousson, & Boissonnas, 2002), in Mexico, the literature is still limited and, in most cases, restricted to PWID who live in Tijuana (Bloom et al, 2021;Fuller et al, 2002;Ben Hamida et al, 2018;Meyers et al, 2021;Mittal et al, 2019;Morris et al, 2012;Rafful et al, 2018;Robertson, Lozada, Pollini, Rangel, & Ojeda, 2012).…”
Section: Introductionmentioning
confidence: 99%